Guided inquiry teaching strategy and students’ performance in redox reaction in Rivers State - Ndukwe, Uju Ethel (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
The study investigated the effect of guided inquiry on students’ performance in redox reactions in senior secondary schools in Obio/Akpor Local Government Area in Rivers State, Nigeria. The study used a non-equivalent group pre-test-post-test quasi-experimental design. The study was led by three (3) research questions and three (3) null hypotheses. 11,920 SSII Science students make up the study's population, which is made up of 5,024 male and 6,896 female students. A total of 132 SS2 pupils from three public senior secondary schools in the Obio-Akpor Local Government Area were included in the sample. They were in their complete classes. Three public schools were chosen, and intact classrooms from each of those schools were also chosen using purposeful sample procedures. The Chemistry Performance Test on Redox Reaction and Mathematics Ability Test, two self-created validated instruments for data collection that were used for the study, had reliability coefficients of 0.88 and 0.76, respectively. The questions were answered using the mean and standard deviation, and the hypotheses were tested using Analysis of Covariance (ANCOVA) at the 0.05 level of significance. The findings indicated that guided inquiry improved student performance more effectively than the lecture method. The study's findings also showed that there were notable differences in the pupils' performance when it came to directed inquiry. In the redox reaction, the male students outperformed the female pupils. Regarding student achievement, there is no discernible joint interplay between strategy and mathematical prowess. The post hoc analysis showed that the significant difference found in the strategy concerning performance was credited to guided inquiry. The study recommended that chemistry teachers should be encouraged to use guided inquiry and virtual laboratory teaching strategies while teaching chemistry.